Analysis of Service Quality on Customer Satisfaction and Switching Intention - Adi, Kurniawan; Safirin, M. T.; Rahadian, Y. R. (Borong Newinera Publisher, 2023)
Boarding houses are small and medium service businesses that provide room rentals, which are an attractive choice for entrepreneurs because they are considered a simple and promising investment if managed well. The demand for temporary housing continues to increase, especially for those who migrate or have routines far from where they live. This research aims to evaluate the influence of variables such as responsiveness, competence, communication, credibility, security, understanding, and tangibles on customer satisfaction in boarding houses in Rungkut District, Surabaya City. The research subjects were boarding house resident in the area, with samples taken using a purposive sampling method for time and cost efficiency. Data was collected through a questionnaire using the Partial Least Square Strucutral Equation Model (PLS-SEM) method. The research results show that a number of variables such as responsiveness, competence, communication, credibility, security, understanding, and tangibles have a significant positive effect on customer satisfaction, both for men, women and all respondents. On the other hand, reliability, access, and courtesy do not significantly influence customer satisfaction. Apart from that, the level of customer satisfaction has also been proven to have a significant negative impact on switching intention.